Tribological Properties of Multilayer DLC/MoS2 Nanocomposite Coatings on Microtextured Titanium Alloy Surfaces - Ke Liu; Qingqing Ding; Hao Peng; Kang Guan; Xiaowan Xi; Ning Kong; Maolin Liao (Lubricants)
Single surface texture or coating technology is gradually unable to produce lasting lubrication of a TC4 titanium alloy in a harsh environment. In order to address this problem, a rectangular microstructure is prepared on the surface of a TC4 titanium alloy by laser processing, and then MoS2/DLC composite interlayer nanocoatings are prepared on the surface by non-equilibrium magnetron sputtering. Friction and wear tests are then carried out on single fabricated, coated and fabricated coatings. The results show that the MoS2/DLC composite interlayered nanocoating can effectively combine with the texture to achieve better friction reduction compared with the single texture and coating. The textured composite coating has the lowest friction coefficient (reduced from 0.4122 to 0.0978) and wear. Through controlled experiments, the textured coating showed good tribological properties at different temperatures and in different friction cycle tests. This study can effectively improve the tribological properties of metal materials through composite coatings, providing research ideas for enhancing the service life of alloys under long-term friction in high-temperature environments.